PENCEGAHAN STUNTING DENGAN PROGRAM DESA TINGGALKAN STUNTING (DESTINTING) DI DESA JEMBAYAN DALAM - Kresna Febriyanto; Candra Wahyu Saputra Azis; Ahmad Juffrianto; Winda Nur Indah Sari; Nur Khalish (Universitas Muhammadiyah Tapanuli Selatan, 2020)
The chronic nutritional problems that occur in toddlers with shorter height characteristics compared to children at their age have called stunting. If children who have stunting in their toddler, then the children have a high risk of getting degenerative diseases as an adult. The purpose of this community empowerment activity is to increase community knowledge about the dangers of stunting so that each family has its cadres. This method of community empowerment used counseling and cadre training and observation sheets, namely pre-test and post-test for questionnaires. Observation sheets that have collected used T-Test for statistic tests. The results of this activity show a pre-test value of 21.67 and Post-Test of 30.71 with a significant increase of 9.04%. There is an increase in community and cadre knowledge after being given counseling. Destination cadre (Village of Leave Stunting) has formed as an effort to monitor the development and growth of Infants. The staff can carry out a Follow-Up plan that is made and has been approved by the head of the village of Jembayan Dalam.